STUDY PENCAHAYAAN ALAMI PADA RUMAH LIMAS PANGGUNG PALEMBANG (Simulasi dengan Program Ecotect 5.0) - Abdul Rachmad Zahrial Amin; Parulian Siregar; JM. Sri Narhadi (Teknoin, 2016)
Sunlight as the largest source of natural light is widely used by humans to carry out their daily activities. Natural light is efficient and saves energy because it does not use electricity. Sometimes humans as light users do not realize how huge the importance of natural light in performing everyday activities as visual comfort. In this study, simulations are conducted on Â Limas Stilt Houses Palembang. This is due to Limas Stilt Houses has existed since Palembang Sultanate era. This study focuses on research related to the opening on the wall of the elements of these houses through the simulation of natural light. The method used in this research is descriptive analysis method based on engineering and architecture discipline of fields. From the simulation results obtained that the 'gegajah' space produced very little natural light ranges from 15-30 lux. This is due to gegajah space is located in the middle of the house and just rely on natural light from the 'bengkilas' Â and 'pawon' rom. While 'bengkilas' and 'pawon' sufficient range of 300-325 lux natural light.